Official Language Minority Communities in Ontario: Understanding the Lived Experiences of Francophone Patients and their Nursing Care Providers - Muray, Mwali (2022)
Although Canada is a bilingual country, official language minority community patients struggle to access quality care in their language. This reality has been of concern for Francophone minority communities in Ontario, but has seldom been examined in a nursing context. This research sought to examine the lived experiences of registered nurses and nursing students providing care to French-speaking patients in Ontario, as well as the realities of Francophone patients seeking French language health care services in Ontario. The conceptual frameworks guiding the study were the “Four Levels of Change for Improving Quality” model and the “Four-Level Model of the Health Care System.” Using qualitative phenomenological inquiry, as influenced by Martin Heidegger and Max van Manen, 31 semi-structured interviews were conducted with three subsets (n=10 Francophone patients; n=10 nursing students; n=11 registered nurses) throughout Ontario who had experience with the phenomenon being investigated. Data collection took place over a year (2018-2019) and was analysed thematically. Significant findings were identified across the three groups. Participants revealed the patchwork of individual actions taking place to remedy the existing gaps regarding care for Francophone minority populations. This included navigating a health care system where good enough care was the unfortunate standard for Francophone patients, and discussing how Francophone patients and nursing care providers implement strategies individually to manage the lack of resources for Francophone patient populations in Ontario. This thesis asserts that official language minority communities and their nursing care providers remain faced with difficulties providing and receiving care in Ontario. While numerous structures and resources exist to remediate the problems, these interventions and resources are not always implemented systemically, leading to a disproportionate burden on individuals, significant risks for safety for patient populations, and ethical dilemmas for nursing care providers. Recommendations are provided to bridge the gaps and ensure considerations of the needs of linguistic minorities throughout the health care system. Keywords: Francophonie, Linguistic Minorities, Nursing, Phenomenology, Qualitative Research

L'accès aux soins de santé des communautés de langue officielle en situation minoritaire (CLOSM) au Canada : une recension des écrits - Muray, Mwali; Peguero-Rodriguez, G.; Scarlett, Emilie; Perron, Amélie; Chartrand, Julie (Minorités linguistiques et société, 2022)
Cette étude présente une recension des écrits sur les expériences des patients et des prestataires de soins en ce qui concerne les services de santé au Canada offerts aux communautés de langue officielle en situation minoritaire (CLOSM). Mandatée par le Bureau d’appui aux communautés de langue officielle (BACLO), cette recension fait constat des défis et des obstacles qui entravent l’offre de services de santé et l’accès aux soins pour les CLOSM dans la langue officielle de leur choix, et propose des recommandations à l’intention des patients, des professionnels de la santé, des établissements de santé, des différents ordres de gouvernement au Canada et des chercheurs. Cette recension des écrits met en lumière le manque d’exécution systémique des stratégies, afin de faciliter l’accès aux services de santé dans leur langue pour les CLOSM fondées sur des données probantes. Elle s’interroge également sur le fait que peu de stratégies fondées sur des données probantes ont été mises en oeuvre à l’échelle du système malgré des décennies de recherche sur le sujet. Mots-clés : accès aux soins de santé, communautés de langue officielle en situation minoritaire (CLOSM), patients, professionnels de la santé, recension des écrits